2020
DOI: 10.1016/j.dam.2019.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Lower bounds for protrusion replacement by counting equivalence classes

Abstract: Garnero et al. [SIAM J. Discrete Math. 2015, 29(4): recently introduced a framework based on dynamic programming to make applications of the protrusion replacement technique constructive and to obtain explicit upper bounds on the involved constants. They show that for several graph problems, for every boundary size t one can find an explicit set R t of representatives. Any subgraph H with a boundary of size t can be replaced with a representative H ∈ R t such that the effect of this replacement on the optimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…One problem of this type arose in the work of Jansen and Wulms on the fixed-parameter tractability of graph optimization problems on graphs of bounded pathwidth [9]. One of their constructions involved the planarization of a nonplanar graph of bounded pathwidth, and they observed that the planarization maintained the low pathwidth of their graph.…”
Section: Introductionmentioning
confidence: 99%
“…One problem of this type arose in the work of Jansen and Wulms on the fixed-parameter tractability of graph optimization problems on graphs of bounded pathwidth [9]. One of their constructions involved the planarization of a nonplanar graph of bounded pathwidth, and they observed that the planarization maintained the low pathwidth of their graph.…”
Section: Introductionmentioning
confidence: 99%